Multiple endometrial polyps in a pre-menopausal woman-sonographic and elastographic findings with histopathological correlation - Paul, Varghese; Phatak, Suresh; Marfani, Gulam; Gupta, Nipun (International Journal of Research in Medical Sciences, 2018)
We are presenting a case report of a 34-year-old female with history of inter-menstrual bleeding PV and Menorrhagia since 6 months with multiple endometrial polyps. Ultrasound and elastography findings are discussed.